Demographic characteristics are associated with children’s nutritional status: Findings from a pilot study on food insecure households in Simunjan district, Sarawak - Tan, Beng Chin; Cheah, Whye Lian; Law, Leh Shii (Nutrition Society of Malaysia, 2023)
Introduction: Food insecurity is a public health concern that may lead to malnutrition in children. The purpose of this study was to determine the relationship between demographic characteristics and food security level with nutritional status among children from food-insecure households in Simunjan District, Sarawak. Methods: This study involved a total of 171 mother-and-child pairs from two Maternal and Child Health Clinics (Simunjan and Gedong) using non-probability convenience sampling technique. Food insecurity status was determined using Radimer/Cornell Hunger Food Insecurity Instrument, while child’s weight and height were measured following standard procedures. Chi-squared test of independence and binary logistic regression were used during data analysis. Results: The prevalences for household food insecurity, individual food insecurity, and child hunger were 70.8%, 15.2%, and 14.0%, respectively. The main nutritional problems for children aged 24–59 months were underweight (17.9%) and stunting (17.9%), while for children aged 60–144 months were overweight and obesity (27.5%). Children of mothers over 34 years old (AOR=2.367; 95% CI: 1.085, 5.164), and those aged 60–144 months (AOR=3.619; 95% CI: 1.521, 8.613) had increased odds of being overweight or obese. Meanwhile, children of working mothers (AOR=6.526; 95% CI: 1.108, 38.449) were more likely to have a thinness problem than children of unemployed mothers. However, no association was found between the severity of food insecurity with children’s nutritional status. Conclusion: Malnutrition in children remains a public health concern in Simunjan District, and it is linked to mother’s age and employment status. An intervention programme is required to ameliorate the situation.